Deficiência de Lipase Ácida Lisossômica (LAL): análise enzimática em papel-filtro como ferramenta diagnóstica em paciente com diagnóstico prévio de doença de Niemann-Pick tipo C - Marcella Borges; Luissa Hikari Hayashi Araujo; Bruno Lima; Laura Vagnini; Alberto Salles; Guerino Pelicer Neto-Magalhães; João Paulo Cristofolo; João Paulo Freitas; Pedro Ivo Aranas; Jacqueline Harouche Rodrigues Fonseca; Fernanda Seabra Souza Timm; Charles Marques Lourenço (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: Lysosomal acid lipase deficiency (LAL-D) is a lysosomal storage disorder involved in cholesterol ester metabolism. It is a poorly understood genetic cause of cirrhosis, dyslipidemia and premature atherosclerotic disease in children and adults. As the manifestations of LAL-D may resemble those observed in other more common diseases, delayed diagnosis is not uncommon. Wolman disease is an early-onset LAL-D phenotype that is usually fatal in the first year of life, but the most common form of the disease may occur at all ages. Recently, enzyme replacement therapy (ERT) for LAL-D has become available. CASE REPORT: A 12-year-old male patient was referred for hepatomegaly. Initially diagnosed as having Niemann-Pick type C disease (NPC), it did not present confirmatory mutations of this disease. Later, with enzymatic dosage of lysosomal acid lipase on filter paper, the diagnosis was redirected to LAL-D (with confirmation in enzymatic dosage in leukocytes and fibroblasts). DISCUSSION: Although LAL-D is considered a rare and uncommon cause of liver disease, recent studies point to a higher prevalence of this disease. Early diagnosis is essential, since specific treatment for this disease is already available. About half of patients with LAL-D die before age 21 in the absence of adequate treatment.